Методика навчання техніці плавання способом «кроль на спині» - Ляшенко, А. М.; Дєлова, І. О.; Поступний, Є. О.; Клімакова, С. М. (Physical Education Theory and Methodology, 2014)
Методика навчання техніці плавання способом «кроль на спині»